Patrimônio ferroviário entre memória e esquecimento: legado da ferrovia no Piauí, 1957-2007 - Vieira, Lêda Rodrigues (Universidade do Vale do Rio dos Sinos, 2024)
Railway transportation was an important part of the social, economic and cultural scene in the cities and towns of Piauí from 1916 to 1980, especially in Teresina and Parnaíba. The railroad is still part of the daily life of the population of Teresina (with the presence of the urban subway and the freight train), while in the other cities in the north of the state, from the 1970s onwards, there was concern about speeches, on the one hand, fighting for the railroads and, on the other, fearful about the end of this transport, until it materialized when the railroad stopped in the 1980s. In order to understand this scenario of the decline of Brazilian rail transport, especially the situation of the Central Railway of Piauí, based on the cities of Teresina and Parnaíba, we analyzed the process of creation and subsequent deactivation of Rede Ferroviária Federal S.A., especially the entry of the state-owned company into the National Privatization Program and, after privatization, the process of liquidation, extinction and inventory of the company's movable and immovable assets. In addition, we analyzed the work of the National Historical and Artistic Heritage Institute (IPHAN) with regard to railway heritage and the public policies for protecting the heritage assets of the Central Railway of Piauí, especially in Teresina and Parnaíba, as well as the possibilities of thinking about the patrimonialization of the photographic collection and the oral memories of railway workers as intangible railway heritage. To do this, we read studies on the history of railroads and railroad heritage, such as those by Francisco Foot Hardman (2005), Manoel Rodrigues Ferreira (2008), Dilma Andrade de Paula (2000), Anna Eliza Finger (2009), Maria Cecília Londres Fonseca (2017) and Maria Emília Lopes Freire (2017). The sources consisted of: newspapers (O Piauí (1950-1960), O Dia (1951-1990), Diário Oficial (1930-1960), Inovação (1977-87), Folha do Litoral (1964-71), Norte do Piauí (1967 and 1968, 1970 and 1973)), periodicals (Almanaque da Parnaíba (1924-1990) and the newspaper O BemBem), government messages and annual reports and statistical yearbooks from Rede Ferroviária Federal S. A, published by the company in the period from 1924 to 1990. A, published by the company between 1958 and 1990, photographs, oral sources and documentation contained in the individual settlement folders of RFFSA employees in São Luís (MA), especially ex-railroad workers who worked on the former Estrada de Ferro Central do Piauí. The time frame of the research covers the years 1957 to 2007, marked by the political, economic and cultural transformations that culminated in the process of discouraging and deactivating rail transportation in Brazil. This time frame is justified because it is the period that sees the consolidation of the rail network into a few public companies and the eradication of uneconomical branches, such as the Central Railroad of Piauí, which led to the retirement and/or transfer to Maranhão of many employees after the railroad's work in northern Piauí was shut down. In addition to the increased use of road transport by the population of Piauí's cities, the new uses and abandonment of a large part of the railway structures, perspectives that have not yet been explored in depth in the historiography on Piauí's railway heritage.
Keywords: RFFSA; Patrimônio ferroviário; Memória ferroviária; Piauí; Railway heritage; Railway memory; ACCNPQ::Ciências Humanas::História